Enhancing Students’ Conceptual Understanding in Mathematics through the Realistic Mathematics Education Model - Amelia putri; Alfi Yunita; Ainil Mardiyah (Tadris Matematika, 2025)
This study investigates the effect of the Realistic Mathematics Education (RME) model on students’ conceptual understanding in mathematics within the framework of the Merdeka Curriculum. Despite curriculum reforms emphasizing student-centered learning, many classrooms remain teacher-centered, resulting in low levels of student engagement and poor conceptual understanding. This quasi-experimental study employed a one-group pretest-posttest design with a quantitative approach. The research involved students from class VIII.6 at MTsN 2 Pesisir Selatan, selected through purposive sampling. A total of four essay-type items were used in both pretest and posttest assessments, targeting three key indicators of conceptual understanding: restating concepts, applying problem-solving algorithms, and representing mathematical ideas in various forms. Data analysis involved normality and homogeneity tests, followed by a paired sample t-test to determine statistical significance. The results showed that students’ posttest scores improved significantly compared to their pretest scores, with a t-value of 18.63 exceeding the critical value at a 5% significance level. Qualitative analysis further supported the quantitative findings, as students demonstrated notable improvement across all indicators. These results suggest that the RME model effectively enhances students' conceptual understanding by fostering contextual learning, active participation, and collaborative problem-solving. The study concludes that RME is a promising instructional model that aligns well with the goals of the Merdeka Curriculum and recommends its broader implementation in mathematics education to improve learning outcomes.